Infrastructure development of agroindustrial complex (Вестник КазНУ. Серия Экономическая, 2016)
In a market economy on the development of the infrastructure of the complex as a whole paid to a lot of attention because it has a significant impact on the results agroindustrial production.Infrastructure development of the agribusiness is seen as an area in which the development of innova tions capable of changing state of the entire agricultural sector.Infrastruc ture agrarian and industrial complex in modern conditions is regarded as an integral element of the infrastructure of AIC, connecting production and consumption of food products.solation of the integral nature of Agrarian and industrial complex infrastructure seems very important, as if some spe cies infrastructural maintenance will be developed sufficiently to meet the needs of agricultural production, while others do not, then improving to achieve the final results of the AIC fail – need a harmonious and balanced development of all infrastructure subsystems.In this article proposes nec essary measures to support infrastructure development of agro-industrial complex by the government.The author proposes measures that contribute to the improvement and development agro-industrial complex.